Structural framework of the Lufilian Fold Belt in the Domes region of North Western Province, Zambia from interpretation of geophysical data. (May 2017) - Williams, P.R.; Nisbet, B.W.
Abstract: The area around the Kabompo and Mwombezhi Domes in the North Western Province of Zambia is characterized by poor outcrop, and as is common with other areas in Zambia, correlation of units between isolated outcrops is complicated by the similarity of lithology in many sections of the stratigraphy. Aeromagnetic data, airborne radiometric and electromagnetic data were used to provide control on correlation between outcrops, and therefore allowed interpretation of a robust structural framework. The two domes are Paleoproterozoic basement-cored anticlines unconformably overlain by Neoproterozoic Roan Group rocks of the lower Katangan Supergroup. The Katangan Supergroup was deposited in an extensional basin formed as part of the breakup of the supercontinent Rodinia. From the geophysical interpretation several normal faults are identified that probably formed during this stage of basin formation, and there is good evidence for at least four regional transfer zones having formed at this time. The fault architecture initiated during the Katangan extensional tectonic event is shown in this interpretation to have strongly influenced the geometry of the Lufilian Fold Belt. Evidence in the domes area suggests that salt tectonics may explain the localization of the regional décollement at the top of the Lower Roan, and provide a structural mechanism for the formation of high-pressure metamorphic rocks in the area. Sinistral reverse faulting and associated folding dominates the Lufilian structural fabric in the east of area, and these faults appear to sole out on the regional décollement. Sigmoidal fold profiles have developed between adjacent fault zones, with east-west oriented fold axes in more distal areas rotating into parallelism adjacent to the faults, suggesting synchronous folding and faulting during north-directed compression. In the north-western part of the study area, fold hinge orientations and basement-cover interactions, indicate north north-westerly directed compression. The study demonstrates that interpretation of combined geological and geophysical mapping at a scale suitable for resolving unit correlations, the deformation sequence and local compression directions, is effective at resolving the extensional and compressional structures that now control the Lufilian Fold Belt structural framework. Highlights: Katangan basin-forming structures are mapped from the interpretation data. Katangan stratigraphy modified to conform to the geophysical information. Northerly Lufilian Arc compression derived from fold orientations, not faults. Lufilian structural "grain" defined by reactivation of Katangan structure. Regional décollement and high pressure metamorphism a result of salt tectonics.